Pidana Perpajakan dalam Perspektif Hukum Islam - Farkhani, Farkhani (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
In some countries, tax is one of the primary incomes for the states revenues. Countries with high tax often have problems from citizens such as tax avoidance, evasion, manipulation and other efforts to reduce their obligation of tax. In Islam, this tax evasion is called as taxjarimah. A person doing tax jarimah can be sentenced with appropriate sanction, based onijtihad and legal reasoning using stipulations derived from al-Qur'an and hadis, which is namedistinbat. In general, tax jarimah can be categorized as jarimah ta'zir. It is a crime where the sanction is determined by goverment or legislative or judicative authorities. This is an exception for corruption case dealing with tax. This jarimah can be considered as jarimahsariqah, in which maximum sanction is hand amputation. However, corruption is an extraordinary crime, which has an extraordinary bad effects. Thus, it is possible that the sanction based on hadud) becomes one of the alternative sanction. The maximum sanction could be more than hand amputation but capital punishment or death sentence.